2015
DOI: 10.3390/s150509791
|View full text |Cite
|
Sign up to set email alerts
|

Novel Monitoring Techniques for Characterizing Frictional Interfaces in the Laboratory

Abstract: A pressure-sensitive film was used to characterize the asperity contacts along a polymethyl methacrylate (PMMA) interface in the laboratory. The film has structural health monitoring (SHM) applications for flanges and other precision fittings and train rail condition monitoring. To calibrate the film, simple spherical indentation tests were performed and validated against a finite element model (FEM) to compare normal stress profiles. Experimental measurements of the normal stress profiles were within −7.7% to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Using the photographic technique, Selvadurai and Glaser [, ] have begun to study the concomitant light changes and foreshock signals emanating from similar regions on the fault, between subsequent frames measured. In this study, we examined the large asperity shown in the 20X magnified image.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the photographic technique, Selvadurai and Glaser [, ] have begun to study the concomitant light changes and foreshock signals emanating from similar regions on the fault, between subsequent frames measured. In this study, we examined the large asperity shown in the 20X magnified image.…”
Section: Resultsmentioning
confidence: 99%
“…Once the film was extracted from the interface, it was scanned to a spatial resolution of 5 µm and processed using MATLAB image recognition algorithms. The image was converted to stresses, and a lower threshold contact stress value was obtained in an iterative manner [ Selvadurai and Glaser , , ]. We assumed that the contact occurred only along the x‐y plane and that the force on each pixel was exactly perpendicular to the plane of the fault.…”
Section: Methodsmentioning
confidence: 99%
“…As discussed in Saltiel et al [], we expect minimal process zone‐related microfracturing. Optical profilometry and pressure sensitive film [ Selvadurai and Glaser , ] were used to characterize the fracture surfaces; these techniques and analysis are described in Saltiel et al []. The imaged contacts transmit shear stress as well as the measured normal stress across the fracture.…”
Section: Methodsmentioning
confidence: 62%
“…Bowden and Tabor () showed that the static friction coefficient is strongly dependent on A c . A c is often studied using transparent materials, such as polymethyl methacrylate, or inferred from indirect measurement, such as fault normal elastic stiffness (Ben‐David et al, ; Dieterich & Kilgore, ; Nagata et al, ; Rubinstein et al, ; Selvadurai & Glaser, ). In this study, we used a novel approach to estimate A c by means of μCT image analysis, using the following steps: Horizontal segmented and pore‐filled binary slices that contained the faults (50 and 70 slices for FL‐I and FL‐II, respectively) were inverted so that the sample material was represented by 0 and air by 1. These inverted slices were then added together through a simple summation of values at the same x ‐ y location (i.e., stacking).…”
Section: Results and Data Analysismentioning
confidence: 99%